Facile Fabrication of y-Fe2O3 Embedded Nanocomposite of Multiwalled Carbon Nanotubes (MWCNTs) - Hasany, Syed Farhan; Nour, A. H.; Kumar, Anuj; Sunarti, Abd Rahman (2013)
Maghemite-embedded multiwelled carbon nanotubes (MWCNTs) nanocomposite structures were fabricated and characterized through facile and reproducible wet method.